2020
DOI: 10.1002/jsfa.10257
|View full text |Cite
|
Sign up to set email alerts
|

Developing a highly selective method for preconcentration and determination of cobalt in water and nut samples using 1‐(2‐pyridylazo)‐2‐naphthol and UV–visible spectroscopy

Abstract: BACKGROUND Heavy metal contamination in water and agricultural products is a major concern that causes risks for human health. This article describes a highly selective approach to preconcentrate cobalt(II) (Co(II)) ions based on the standard UV–visible measurement of Co(II)–1‐(2‐pyridylazo)‐2‐naphthol complex at λ = 628 nm in water and nut samples. In this method, magnetic silica (mSiO2) was utilized as a practical sorbent and 1‐(2‐pyridylazo)‐2‐naphthol was employed as a complexing agent in the elution step.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Environmental waters may become contaminated with cobalt due to both human activities and natural sources. 4 Consequently, the development of accurate and rapid measurement methods for cobalt in diverse sample types is imperative. Among numerous analytical techniques employed to determine cobalt levels, graphite furnace atomic absorption spectrometry (GFAAS), inductively coupled plasma (ICP), 5 flame atomic absorption spectroscopy (FAAS), 6 inductively coupled plasma mass spectrometry (ICP-MS), 7 inductively coupled plasma optical emission spectroscopy (ICP-OES), 8 and UV-Vis spectrometry 9 can be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental waters may become contaminated with cobalt due to both human activities and natural sources. 4 Consequently, the development of accurate and rapid measurement methods for cobalt in diverse sample types is imperative. Among numerous analytical techniques employed to determine cobalt levels, graphite furnace atomic absorption spectrometry (GFAAS), inductively coupled plasma (ICP), 5 flame atomic absorption spectroscopy (FAAS), 6 inductively coupled plasma mass spectrometry (ICP-MS), 7 inductively coupled plasma optical emission spectroscopy (ICP-OES), 8 and UV-Vis spectrometry 9 can be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of this metal at low levels is critical because cobalt is carcinogenic at high doses. 4,5 In the literature, there are several studies reported for the determination of cobalt in different matrices such as inductively coupled plasma optical emission spectrometry (ICP-OES), 6 inductively coupled plasma mass spectrometry (ICP-MS), 7 graphite furnace atomic absorption spectrometry (GFAAS), 8 ultraviolet-visible spectrophotometry (UV-vis), 9 digital image colorimetry, 10 stripping voltammetry, 11 and ame atomic absorption spectrometry (FAAS). 12 Among the aforementioned methods, FAAS is preferred by many research laboratories in heavy metal determination because of its outstanding features such as short analysis times, easy and inexpensive operation, and not requiring complicated mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This is a threat to public health. This adulteration is not only limited to milk but can also be observed in other foods like olive oil, honey, saffron, orange juice, coffee, apple juice, and nuts 2–11 . Milk has been reported to be adulterated by inexpensive, inferior quality, and harmful chemical substances to increase the volume, mask the quality parameters (e.g., protein and fat content), and prolong the product's shelf life 11–13 …”
Section: Introductionmentioning
confidence: 99%